The Use of Land: some Aspects - Das, B. L. (Indian Forester, 1963)
The problem of proper land use for increasing production has become important in the country in recent years. The paper deals with some aspects of land use both in agriculture and forestry practices and also describes some of the observations made by the author in Europe and U.S.A. during 1960-61.